Parametric study for optimizing fiber-reinforced concrete properties - Khalel, Hamad Hasan Zedan; Khan, Muhammad; Starr, Andrew G.; Sadawi, Noureddin; Mohamed, Omar Ahmed; Khalil, Ashraf; Esaker, Mohamed (Wiley, 2025)
Concrete with fiber reinforcement is stronger and more ductile than concrete without reinforcement. Significant efforts have been made to demonstrate the properties and enhancements of concrete after reinforcement with various types and shapes of fibers. However, the issue of optimization in the reinforcement process is still unanswered. There is no academic study in the literature now available that can pinpoint the ideal fiber type, quantity, and shape and, more crucially, the overall technical viability of the reinforcement. The parametric analysis in this study determines the ideal shape, size, and proportion of fibers. The input and output parameters were separated from the optimization design variables. Input parameters included assessment of samples of fresh and mechanical concrete properties and the influence of type, length, and percentage of fiber on concrete performance. The aim was to establish the most efficient relationship between fiber dose and dimension to optimize the combined responses of workability and splitting tensile, flexural, and compressive strength. The mechanical and fresh properties of concrete reinforced with four different fibers, PFRC-1, PFRC-2, SFRC-1, and SFRC-2, were tested. The analysis showed that SFRC-2-20 mm-1%, with compressive, split tensile, flexural, and workability values of 44.7 MPa, 3.64 MPa, 5.3 MPa, and 6.5 cm respectively, was the most effective combination among the materials investigated. The optimization technique employed in this study offers new, important insights into how input and output parameters relate to one another.
Keywords: fiber; mechanical properties; optimizing; reinforced concrete